A comprehensive review of Project-Based Learning (PBL): Unravelling its aims, methodologies, and implications - Nazula Silma; Ikrima Maulida; Adisti Primi Wulan; Joyce Merawati; Md. Kamrul Hasan (PT. MAWAMEDIA JAYAMUSTA BUANASIHA, 2024)
This review delves into the multifaceted realm of Project-Based Learning (PBL), aiming to provide a comprehensive understanding of its objectives, methodologies, and implications. The study draws on a meticulous examination of existing literature through document analysis and the review of researches centred on PBL. The primary aim of the research is to discern the key objectives pursued by educators and institutions employing PBL as a pedagogical approach. The method of data collection involves an extensive review of scholarly articles, academic papers, and educational reports, spanning various disciplines and educational levels. By synthesizing information from diverse sources, this study aims to construct a nuanced picture of the aims that PBL seeks to achieve, encompassing cognitive, affective, and skill-based learning outcomes. The analysis phase employs a qualitative approach to identify recurring themes, patterns, and variations in the aims of PBL across different educational contexts. Additionally, the study scrutinizes the methodologies adopted in various researches to assess the effectiveness of PBL, examining factors such as project design, assessment strategies, and student engagement. The findings reveal a range of objectives associated with PBL, including fostering critical thinking skills, enhancing collaboration, and promoting real-world applicability of knowledge. Furthermore, the analysis sheds light on the diversity of methodologies employed in PBL research, showcasing the adaptability of this pedagogical approach across disciplines and educational settings. In conclusion, this review consolidates the aims of PBL, highlights the varied methodologies used to assess its impact, and discusses the implications for future educational practices. By synthesizing current knowledge on PBL, this study contributes to the ongoing dialogue surrounding effective pedagogical strategies, providing insights for educators, researchers, and policymakers seeking to optimize learning experiences through project-based approaches.